Determining the influence of seasonal tilt angle on the efficiency of fixed solar photovoltaic modules - Golub, Gennadii; Tsyvenkova, Nataliya; Nadykto, Volodymyr; Marus, Oleh; Kepko, Oleg; Omarov, Ivan; Holubenko, Anna; Shubenko, Vladyslav; Zayets, Maksym (Eastern-European Journal of Enterprise Technologies, 2024)
The object of this study is photovoltaic modules with different seasonal tilt angles at different geographical latitudes. The average annual efficiency of photovoltaic modules with different seasonal angles set at different geographical latitudes has been determined as the annual weighted average value of the cosine of the angle of incidence of solar rays on the plane of the photovoltaic module. The influence of seasonal tilt angles of photovoltaic modules at different geographical latitudes on their average annual efficiency was analyzed. Approximate values of the seasonal tilt angles of photovoltaic modules at different geographic latitudes take values that differ from the geographic latitude value by plus 15° for the winter period and minus 15° for the summer period. Modeling the average annual efficiency of photovoltaic modules depending on the seasonal tilt angles at different geographical latitudes made it possible to obtain refined values of the seasonal tilt angles of photovoltaic modules. Thus, at the latitude of 0°, 10°, 20°, 30°, 40°, 50°, and 60°, the tilt angle of photovoltaic modules for the winter period will be 14.8°, 24.6°, 34.5°. 44.4°, 54.1°, 63.6°, and 73°, respectively, and for summer ‒ minus 14.5°, minus 4.6°, 5°, 15.1°, 25.1°, 34.9°, and 44.7°. Dependences were obtained for determining the seasonal tilt angles of photovoltaic modules depending on the value of geographic latitude. The difference in the average annual efficiency of photovoltaic modules, which are installed at seasonal angles, and photovoltaic modules, which track the position of the Sun in the vertical plane, is 0.4 %. The results could be used as a basis for evaluating the efficiency of photovoltaic modules when determining the seasonal tilt angle at different geographic latitudes